2015
DOI: 10.1186/s13148-015-0152-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation profiling of CD8+ T cells shows a distinct epigenetic signature to CD4+ T cells in multiple sclerosis patients

Abstract: BackgroundMultiple sclerosis (MS) is thought to be a T cell-mediated autoimmune disorder. MS pathogenesis is likely due to a genetic predisposition triggered by a variety of environmental factors. Epigenetics, particularly DNA methylation, provide a logical interface for environmental factors to influence the genome. In this study we aim to identify DNA methylation changes associated with MS in CD8+ T cells in 30 relapsing remitting MS patients and 28 healthy blood donors using Illumina 450K methylation arrays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 15 publications
2
78
2
Order By: Relevance
“…Moreover, genomewide DNA methylation studies have identified DMRs of CD4 T cells in MS patients compared to healthy controls, specifically on chromosome 6p21 at HLA‐DRB1 (a known MS risk locus), and additional non‐HLA CpGs that localized to genes linked with MS . Interestingly, the methylation profile of CD8 T cells in the same cohort of patients with relapsing remitting MS differed from CD4 T cells, supporting the notion that it is important to consider cell type‐specific epigenetic regulation . Mouse models of MS illustrate how targeting epigenetic mechanisms can also contribute to the design of novel therapies.…”
Section: Epigenetics Of T Cells In Autoimmunitymentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, genomewide DNA methylation studies have identified DMRs of CD4 T cells in MS patients compared to healthy controls, specifically on chromosome 6p21 at HLA‐DRB1 (a known MS risk locus), and additional non‐HLA CpGs that localized to genes linked with MS . Interestingly, the methylation profile of CD8 T cells in the same cohort of patients with relapsing remitting MS differed from CD4 T cells, supporting the notion that it is important to consider cell type‐specific epigenetic regulation . Mouse models of MS illustrate how targeting epigenetic mechanisms can also contribute to the design of novel therapies.…”
Section: Epigenetics Of T Cells In Autoimmunitymentioning
confidence: 88%
“…Scandinavian Journal of Immunology, 2017, 86,[184][185][186][187][188][189][190][191][192][193][194][195] 190 Epigenetics of T-Cell Differentiation genes linked with MS [77]. Interestingly, the methylation profile of CD8 T cells in the same cohort of patients with relapsing remitting MS differed from CD4 T cells, supporting the notion that it is important to consider cell type-specific epigenetic regulation [78]. Mouse models of MS illustrate how targeting epigenetic mechanisms can also contribute to the design of novel therapies.…”
Section: Epigenetics Of T Cells In Autoimmunitymentioning
confidence: 89%
“…DNA methylation has been shown to regulate key aspects of CD8 + T-cell function, including cellular differentiation and exhaustion 7 . Moreover, epigenetically mediated alterations in T-cell function have been implicated in disease pathogenesis of several immune mediated conditions 6,25,26 . We performed genome-wide DNA methylation profiling of CD8 + T-cells derived from children newly diagnosed with CD (n=66).…”
Section: Cd8 + T-cell Dna Methylation Shows Association With Age But mentioning
confidence: 99%
“…PAD-2 destabilizes the myelin basic protein (MBP), which becomes an antigen for T cells [11]. Most recently, genome-wide DNA methylation profiling of CD8+ T and CD4+ T cells has shown distinct DNA methylation profiles in relapsing-remitting (RRMS) compared to healthy controls [12]. Importantly, methylation patterns of cell-free plasma DNA has been proposed as potential biomarkers for MS [13].…”
Section: Introductionmentioning
confidence: 99%